THE IMPORTANCE OF AUTONOMOUS WORK IN THE CREDIT MODULE SYSTEM - Xolmatov, Shokirjon (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article discusses the penetration of the credit-module system into higher educational institutions of the Republic of Uzbekistan, its positive aspects and principles, the importance of autonomous work and study in the credit-module system, its types and forms, and the purpose of autonomous education, as well as the tasks of the student and teacher in autonomous education. In addition, it also considers the elements in the organization of students’ autonomous work.
Keywords: Credit Module System; self study; educational process; self-assessment; teaching material; important principles; types of autonomous education